Assessment of the nanoleakage between different adhesive systems and deproteinized dentin with Nd:YAG laser and 10% NaOCl - Raad DAYEM (International Arab Journal of Dentistry (IAJD), 2013)
The objective of this study was to evaluate the global leakage scores on the interface between two adhesive systems and the acid-etched dentin and to estimate the nanoleakage after removing the collagen network by Nd:YAG laser or 10% NaOCl. Thirty extracted human upper premolars were selected to receive standardized buccal and lingual class V cavities. The teeth were randomly divided into two groups of fifteen teeth each: in the first group, the Excite® bonding system was used, whereas in the second group, the Solobond Plus adhesive system was applied. In each group, teeth were equally allocated to one of the following treatments prior to bonding application: a) acid etching / Nd:YAG laser; b) acid etching /10% NaOCl and c) acid etching. Global leakage score of each specimen was calculated as the percent of the total cut dentin surface penetrated by silver nitrate. The results showed that treating the acid etched-dentin with Nd:YAG laser led to a significant decrease in the global leakage scores; these latter were significantly less than those of acidetched / 10% NaOCl treated dentin. The Excite® bonding system showed higher global leakage scores than the Solobond Plus bonding system.